Growth characteristics of two tropical forest species Warburgia ugandensis and Polyscias fulva seedlings grown under contrasting light conditions - J. I. Kinyamario; T. P. Wang’ombe; J. Wanyondu (Global Journal of Food and Agribusiness Management, 2019)
Growth parameters for seedlings of two forest trees, Warburgia ugandensis and Polyscias fulva, were measured under various light growth conditions. Leaf area and plant height were significantly higher under low light (< 42% full sunlight) than high light (65% of sunlight) growth conditions (P<0.001). Plant leaf area ranged from 238 cm² under full sunlight to 376 cm² under dense shade in P. fulva and from 33 cm² under full sunlight to 178 cm² under dense shade in W. ugandensis. Plant heights ranged from about 20 mm under full sunlight to 38 mm under dense shade in P. fulva; and from about 36 mm under full sunlight to 89 mm under dense shade in W. ugandensis. P. fulva had more leaves than W. ugandensis but both species increased their leaf numbers from 28 (full sunlight) to 37 (dense shade) and 21 (full sunlight) to 29 (dense shade) respectively (P< 0.05). P. fulva accumulated more biomass (from 4 to about 9g) than W. ugandensis (from 0.6 to 2.4g) under all light conditions (P<0.05). The shoot/root ratios were highest (1.84 for P. fulva and 6.42 for W. ugandensis) under low light conditions in the two species (P<0.05). Highest specific leaf areas were recorded under low light growth conditions (198 cm² g-1 for P. fulva and 220 cm² g-1 for W. ugandensis). W. ugandensis was found to be more shade tolerant than P. fulva.